2021
DOI: 10.1097/sla.0000000000005115
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Open, Robotic, and Thoracoscopic Lobectomy (PORTaL) Study

Abstract: Objective: The aim of this study was to analyze outcomes of open lobectomy (OL), VATS, and robotic-assisted lobectomy (RL). Summary Background Data: Robotic-assisted lobectomy has seen increasing adoption for treatment of early-stage lung cancer. Comparative data regarding these approaches is largely from single-institution case series or administrative datasets. Methods: Retrospective data was collected from 21 institutions from 2013 to 2019. All consecutive cases performed for clinical stage IA-IIIA lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 17 publications
(37 reference statements)
0
52
1
1
Order By: Relevance
“…Compared to thoracotomy, VATS lung resection [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] in two randomized controlled trials [ 7 , 12 , 13 ] or RATS lung resection [ 11 , 14 , 15 , 16 , 17 , 18 , 19 ] led to better short-term outcomes, fewer adverse events, shorter hospital stays, and lower morbidity and mortality rates. Regarding short-term outcomes, the superiority of VATS or RATS is still debated in one randomized controlled trial [ 20 ] and in systematic reviews and meta-analysis and propensity-matched cohorts [ 11 , 14 , 15 , 18 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to thoracotomy, VATS lung resection [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] in two randomized controlled trials [ 7 , 12 , 13 ] or RATS lung resection [ 11 , 14 , 15 , 16 , 17 , 18 , 19 ] led to better short-term outcomes, fewer adverse events, shorter hospital stays, and lower morbidity and mortality rates. Regarding short-term outcomes, the superiority of VATS or RATS is still debated in one randomized controlled trial [ 20 ] and in systematic reviews and meta-analysis and propensity-matched cohorts [ 11 , 14 , 15 , 18 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…For long-term outcomes, overall survival (OS) and disease-free survival (DFS) are the main criteria of oncological quality to evaluate the resection performed for all cancers. No difference was reported when a minimally invasive approach, such as VATS or RATS, was compared with open surgery [ 11 , 14 , 15 , 18 , 21 , 22 , 23 , 24 ]. More than enhanced recovery, VATS and RATS also preserve long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…e previous studies have reported mean blood loss of 87 cc and 170 cc during robotic-and video-assisted lobectomy, respectively; however, in patients with dense pleural adhesions, intraoperative blood loss is higher and can range from 200 to 500 cc. [9,10] In comparison, a reduction in intraoperative blood loss, 50 cc, was observed during roboticassisted lobectomy post-embolization in Case 1. e 400 cc of intraoperative blood loss observed in Case 2 is more difficult to evaluate due to the patient's dense pleural adhesions and conversion to open thoracotomy, but it is likely that preoperative embolization still provided intraoperative benefit due to the complicated nature of the case.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, case reports of successful embolization have now been described in adults. [1][2][3][4][5][6][7][8][9][10][11] We report two cases of endovascular embolization that further illustrates the utility of emergently stopping hemoptysis, allowing for delayed surgical intervention for pulmonary sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, the influence of blood vessel variation, peripheral inflammation and adhesion in recurrent PAVMs may increase the risk of surgery and extreme blood loss. The Da Vinci robot, with its flexible manipulator arm and 3D surgical field, has a huge advantage in tackling these problems [ 8 ]. Therefore, we think that local excision, segmentectomy or lobectomy by using Da Vinci robot is a safe method for recurrent and complex PAVMs.…”
Section: Discussionmentioning
confidence: 99%